Nueva especie de (sauria: iguanidae) lagarto collarejo de la zona sur andina de colombia (1982)
Two species of the Andean lizard genus Stenocercus are reported from Colombia, in addition to the well-known S. trachycepbalus. The presence of Stenocercus guentheri, group lizards in the southern Departamento de Nariño is confirmed. A new species of Stenocercus is described from the immediate surroundings of the town of Bolivar, Departamento del Cauca.